2018
DOI: 10.1016/j.jfludis.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of emotion on articulation rate in persistence and recovery of childhood stuttering

Abstract: Negative emotion plays a detrimental role on the speech-motor control processes of children who persist, whereas children who eventually recover seem to exhibit a relatively more stable and mature speech-motor system. This suggests that complex interactions between speech-motor and emotional processes are at play in stuttering recovery and persistency; and articulation rates following negative emotion or during stuttered versus fluent speech might be considered as potential factors to prospectively predict per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 124 publications
0
18
0
1
Order By: Relevance
“…In turn, increased arousal leads to increased instability in the speech motor sys-tem. Erdemir et al 48 reported promising results showing that compared with CWNS and CWS-Rec, CWS-Per had slower articulation rates when generating a narrative describing a video clip eliciting negative emotion. They suggest that articulation rates following nega-tive emotional stimuli in preschool CWS could be a factor that predicts persistence/recovery from stuttering.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, increased arousal leads to increased instability in the speech motor sys-tem. Erdemir et al 48 reported promising results showing that compared with CWNS and CWS-Rec, CWS-Per had slower articulation rates when generating a narrative describing a video clip eliciting negative emotion. They suggest that articulation rates following nega-tive emotional stimuli in preschool CWS could be a factor that predicts persistence/recovery from stuttering.…”
Section: Resultsmentioning
confidence: 99%
“…These storybooks are frequently used for storytelling tasks in studies. (Choi et al, 2016;Erdemir, Walden, Jefferson, Choi, & Jones, 2018).…”
Section: Storytelling Taskmentioning
confidence: 99%
“…Stuttering is a speech disorder which can be affected by emotions [8][9][10]. It is suggested that stuttering behaviors change during an emotional situation, especially in CWS [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that stuttering behaviors change during an emotional situation, especially in CWS [9]. Furthermore, negative emotions could slow articulation rates in children with persisting stuttering; however, it is not an influential factor in recovered and Typically-Developing Children (TDC) [10]. It remains unclear how emotional content can change fluency, as there is no concise electrophysiological evidence in this respect.…”
Section: Introductionmentioning
confidence: 99%